2023
DOI: 10.1021/acsomega.3c08128
|View full text |Cite
|
Sign up to set email alerts
|

AI-Based Geometry Recognition for Evaluating the Feasibility of Intensified Reaction and Separation Systems

Yongbeom Shin,
Minyong Lee,
Jeongwoo Lee
et al.

Abstract: Reactive distillation (RD) provides notable advantages over conventional processes, regarding reduced energy requirements and CO 2 emissions. However, as the benefits of RD may not be universally applicable, a comprehensive feasibility assessment is necessary. This study introduced an automated feasibility evaluation procedure for an RD column using an AI-based region recognition approach, reducing the reliance on expert knowledge and heuristics in graphical methods. Through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…The hindrance in achieving a high-purity SM product through distillation arises not only from the closely aligned boiling points of components but also from the formation of an azeotrope among these components. , A prior study reported that an azeotrope does not form between alpha-methylstyrene (AMS) and SM under vacuum pressure conditions, but an azeotrope can be formed at atmospheric pressure . In this study, we employed the UNIQUAC thermodynamic model, which is suitable for predicting the behavior of aromatic components in Aspen Plus, to investigate the formation of azeotropes among all components across the whole range of pressures (refer to the binary interaction parameters in Table S2).…”
Section: Simulation Environments and Methodsmentioning
confidence: 99%
“…The hindrance in achieving a high-purity SM product through distillation arises not only from the closely aligned boiling points of components but also from the formation of an azeotrope among these components. , A prior study reported that an azeotrope does not form between alpha-methylstyrene (AMS) and SM under vacuum pressure conditions, but an azeotrope can be formed at atmospheric pressure . In this study, we employed the UNIQUAC thermodynamic model, which is suitable for predicting the behavior of aromatic components in Aspen Plus, to investigate the formation of azeotropes among all components across the whole range of pressures (refer to the binary interaction parameters in Table S2).…”
Section: Simulation Environments and Methodsmentioning
confidence: 99%